Maternal satisfaction towards intrapartum care of designated healthcare facilities and its associated factors among postnatal women attending Klinik Kesihatan Salak - Mohamad, Fadzilah; Lee, Ping Yein; Mawardi, Maliza (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: The World Health Organization recommends evaluation of maternal satisfaction to improve quality of health care during childbirth. Dissatisfaction may lead to undesired outcomes such as unassisted homebirth and delay in seeking treatment. Determining the maternal satisfaction level and its associated factors may help to improve health care services and prevent negative implications to both mothers and infants. This study aimed to determine the maternal satisfaction towards intrapartum care of designated healthcare facilities and its associated factors among postnatal women. Methods: This was a cross-sectional study of postnatal women attended Klinik Kesihatan Salak from December 2017 to February 2018. Systematic random sampling with the ratio of 1:3 was applied to the eligible respondents. A self-administered questionnaire that include respondent’s socio-demographic characteristics and a validated 14-items Maternal Satisfaction with Hospital-based Intrapartum Care Scale was used. Data was analyzed using SPSS 23. Results: 274 respondents were recruited in this study. Overall, only 21.2% of respondents were satisfied with the intrapartum care given. The level of satisfaction was highest in interpersonal care domain (36.1%), followed by physical birth environment (34.3%) and the least satisfied was information and decision making domain (27.7%). Binary logistic regression showed that maternal satisfaction was significantly associated with place of birth (AOR (95% CI): 0.046 (0.183, 0.984)) and labour complications (AOR (95% CI): 3.387 (1.345, 8.528)). Conclusion: The overall maternal satisfaction towards intrapartum care was low and the information and decision-making domain appeared to be the least satisfied. Maternal satisfaction was associated with place of birth and labour complications. Therefore, health care providers should emphasize and improve the quality of services especially for this domain and to consider factor that contribute to dissatisfaction towards the intrapartum care.